Hepatic function of glucagon-like peptide-1 and its based diabetes drugs - Feng, Jia Nuo; Jin, Tianru (Medical Review, 2024)
Incretins are gut-produced peptide-hormones that potentiate insulin secretion, especially after food intake. The concept of incretin was formed more than 100 years ago, even before insulin was isolated and utilized in the treatment of subjects with type 1 diabetes. The first incretin, glucose-dependent insulinotropic polypeptide (GIP), was identified during later 1960’s and early 1970’s; while the second one, known as glucagon-like peptide-1 (GLP-1), was recognized during 1980’s. Today, GLP-1-based therapeutic agents [also known as GLP-1 receptor (GLP-1R) agonists, GLP-1RAs] are among the first line drugs for type 2 diabetes. In addition to serving as incretin, extra-pancreatic functions of GLP-1RAs have been broadly recognized, including those in the liver, despite the absence of GLP-1R in hepatic tissue. The existence of insulin-independent or gut-pancreas-liver axis-independent hepatic function of GLP-1RAs explains why those therapeutic agents are effective in subjects with insulin resistance and their profound effect on lipid homeostasis. Following a brief review on the discovery of GLP-1, we reviewed literature on the exploration of hepatic function of GLP-1 and GLP-1RAs and discussed recent studies on the role of hepatic hormone fibroblast growth factor 21 (FGF21) in mediating function of GLP-1RAs in animal models. This was followed by presenting our perspective views.